Application of Arbuscular Mycorrhizal Fungi on Several Types of Phytoremediation Plants to Reduce Lead (Pb) Contaminants in Rice Fields - Kumalawati, Zahraeni; Tahang, Jumrawati; Kafrawi; Nontji , Maimuna (Asosiasi Mikoriza Indonesia, 2025)
The use of chemical compounds in intensive agricultural systems triggers an increase in residual heavy metal compounds such as Pb and has the potential to be a pollutant in the soil and water environment. This study aims to test the effectiveness of several types of phytoremediation plants in absorbing lead (Pb) with the application of arbuscular mycorrhizal fungi originating from two different types of land (rice fields and dry land).The research method used a factorial design based on a Randomized Group Block Design, consisting of two factors, namely the type of mycorrhizal isolate originating from rice fields and dry land, and three types of phytoremediation plants, namely sunflowers, napa cabbage (Brassica pekinensis L.) and citronella (Cymbopogon nardus L.), with three replications and two plants units totaling 54 experimental units. The results showed that mycorrhiza from rice fields increased the percentage of Pb compound absorption capacity of phytoremediation plants compared to mycorrhiza from rice fields. The growth of phytoremediation plants tends to be better with the presence of mycorrhiza symbiosis. Sunflowers have the highest average Pb absorption capacity of 73%, while citronella can absorb Pb well even without mycorrhiza.